2021
DOI: 10.1021/jacs.1c00288
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Oxidation Enables Regioselective and Scalable α-C(sp3)-H Acyloxylation of Sulfides

Abstract: A highly selective, environmentally friendly, and scalable electrochemical protocol for the construction of α-acyloxy sulfides, through the synergistic effect of self-assembly-induced C­(sp3)–H/O–H cross-coupling, is reported. It features exceptionally broad substrate scope, high regioselectivity, gram-scale synthesis, construction of complex molecules, and applicability to a variety of nucleophiles. Moreover, the soft X-ray absorption technique and a series of control experiments have been utilized to demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 62 publications
1
23
0
1
Order By: Relevance
“…Subsequently, Pd, Cu, Co, Ru, and Rh catalyst systems have been developed for the C–H oxygenation reactions. In addition, Mei and Ackermann ,, independently demonstrated that the chemical oxidant can be replaced by the electricity means for the same conversion . However, the application of readily accessible organic oxyanion reagents in this approach has been often hampered by the kinetically demanding reductive elimination as well as an undesired ligand dissociation, mainly because of the pronounced metal–oxygen bond polarity (Scheme b). , While a range of C–H oxygenation reactions has been revealed by various procedures, their synthetic applications are often limited mainly because of the use of excessive amounts of oxygen sources.…”
mentioning
confidence: 99%
“…Subsequently, Pd, Cu, Co, Ru, and Rh catalyst systems have been developed for the C–H oxygenation reactions. In addition, Mei and Ackermann ,, independently demonstrated that the chemical oxidant can be replaced by the electricity means for the same conversion . However, the application of readily accessible organic oxyanion reagents in this approach has been often hampered by the kinetically demanding reductive elimination as well as an undesired ligand dissociation, mainly because of the pronounced metal–oxygen bond polarity (Scheme b). , While a range of C–H oxygenation reactions has been revealed by various procedures, their synthetic applications are often limited mainly because of the use of excessive amounts of oxygen sources.…”
mentioning
confidence: 99%
“…A scalable electrochemical protocol for the synthesis of α ‐acyloxy sulfides of the type 184 was proposed by Lei with coworkers. [ 115 ] The substrate scope of this method was extremely broad, which enabled the synthesis of more than 140 compounds, including pharmaceutical scaffolds that are quite difficult to access by other techniques (Scheme 29). The key feature of this method was the self‐assembly of reaction substrates after MeOH addition, with subsequent anodic oxidation of the sulfide of the type 183 , followed by nucleophilic attack of the acid at the resulting carbocation.…”
Section: Electrochemical Acyloxylationsmentioning
confidence: 99%
“…Based on recent report from our group on the electrochemcial oxidation strategy, [ 7 ] we hypothesised whether such a strategy could be used to activate the amino acids with the use of DMS as mediator with the help of anodic electrochemistry (Figure 1). If successful, acids would be transformed into an intermediate I containing a sulfide unit, followed by the oxidation of sulfur atom to form an activative intermediate II , which is sensitive to nucleophilic substances.…”
Section: Background and Originality Contentmentioning
confidence: 99%